Społeczno-kulturowe uwarunkowania demokratyzacji edukacji na Tajwanie - Nowosad, Inetta (Kultura-Społeczeństwo-Edukacja, 2018)
Nowosad Inetta, Społeczno-kulturowe uwarunkowania demokratyzacji edukacji na Tajwanie [Social and cultural preconditions for the process of democratization in Taiwanese education]. Kultura – Społeczeństwo – Edukacja nr 2(14) 2018, Poznań 2018, pp. 137–154, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2018.14.12. The article focuses on changes introduced in Taiwan’s education since 1949, which reflect the social changes taking place in this country. Special attention is drawn to the origin and the course of two particularly important processes, i.e. democratisation and taiwanisation, which have radically changed the face of education, revealing Taiwan’s ‘balancing’ between the East and the West. While depicting their essence, also complex links with Taiwan’s policies towards China and its orientation onto economic growth were taken into account.